PREVALENSI PASIEN COVID-19 DENGAN PENYAKIT KOMORBID DI SEMEN PADANG HOSPITAL TAHUN 2020 - Vani, Ade Teti; Rustam, Raihana; Amran, Rika; Dewi, Nadia; Ulfa, Febrina (Nusantara Hasana Berdikari, 2022)
The severity of patients confirmed positive for COVID-19 can be influenced by comorbid diseases in patients. This comorbid disease can cause a decrease in the patient's immune system than patients who do not have a comorbid disease. To determine the prevalence of COVID-19 patients with comorbid diseases at Semen Padang Hospital in 2020. The most gender was male, namely 55 people (56.7%), the average age was 54 years, with a median value of 55 and a mode value of 55, the highest degree of COVID-19 was moderate, namely 53 people (54.6% ), and the most comorbid hypertension was 49 people (50.5%). Most of the sexes are male, the average age is 54 years, the highest degree of COVID-19 is moderate, and the most comorbid is hypertension.